(untitled) (Sir Salimullah Medical College Journal, 2025)
Background: Decompensated cirrhosis of liver may lead to renal hypoperfusion and dysfunction that may be predicted by urinary albumin-to-creatinine ratio (UACR) and this UACR value may be one of the predictors of severity of liver disease. The aim of the study was to determine the relationship of urinary albumin creatinine ratio with severity of liver disease in patients with decompensated cirrhosis of liver. Methods: A cross-sectional observational study was carried out in the Department of Hepatology, Bangladesh Medical University (Former - BSMMU), Dhaka on 100 patients of decompensated cirrhosis of liver of different etiology. Patients were divided into two groups as based on UACR ≤30mg/g (group 1) and UACR ≥30 mg/g (group 2). The groups were compared of cirrhosis related features, complications, CTP, (Child-Turcotte-Pugh) score and Model for end-stage liver disease (MELD) score. A receiver-operator characteristic curve was used for prediction of UACR with CTP class. Results: Male female ratio was 3:2. Sixty six (66%) patients had hepatitis B. Mean CP score 9.34±1.2, mean MELD score 20.6±6.96, mean urinary creatinine 81.5±78.0, urinary microalbumin 31.5±37.33 and mean UACR was 41.86±43.96. The difference was statistically significant (p<0.05) between two groups. ROC curve was constructed by using UACR, which gave a cut off value 32.43mg/g, with 78.3% sensitivity and 81.5% specificity for severity of decompensated liver diseases termed by Child Pugh Class C. Conclusion: This study shows microalbuminuria measured by UACR, at ≥ 32.43mg/g level is associated with more severity in patients with decompensated cirrhosis of liver and positively correlated with CTP score and MELD score. Sir Salimullah Med Coll J 2024; 32: 70-75